INCREASING LEARNING OUTCOMES READING BY CLASS 1 STUDENTS OF SDN 24 BANDA ACEH WITH THE "GULINGJAR" STRATEGY - Ridhayanie, Ridhayanie; Sari, Siti Mayang (Sensei International Journal of Education and Linguistic, 2024)
School is a place for all students to receive learning according to their needs. Learning is an educational tool that can hone every child's abilities in both writing and reading skills. By reading, students can put information into their notebooks. However, less than optimal interest in reading can have an impact on students' ability to master reading skills. Therefore, it is important to understand the factors that cause low interest in reading among grade 1 students and find innovative solutions to increase their interest and reading ability. This research aims to increase the interest and reading ability of grade 1 students through the application of the "rolljar" strategy. With a focus on the low interest in reading among grade 1 students. This research uses a qualitative approach with descriptive research type. The research results show that the "rolljar" strategy, especially with visits to the Aceh Regional Library, is effective in increasing students' interest in reading. With collaboration between teachers, parents and students, it is hoped that this strategy can be an effective alternative in improving reading learning at the initial level of education.